The MeSH heading “Call Center” is due for an update: why we recommend the more precise heading “Emergency Medical Communication Center” - Harring, Astrid K. V.; Blinkenberg, Jesper; Brattebø, Guttorm; Hjortdahl, Magnus; Idland, Siri; Iversen, Emil; Leonardsen, Ann-Chatrin. L.; Zakariassen, Erik; Jørgensen, Trine M. (Scandinavian journal of trauma, resuscitation and emergency medicine, 2023)
Call centers can be found in various industries. However as a Medical Subject Heading (MeSH) the term “Call centers” does not reflect the critical purpose of handling emergency calls. We recommend “emergency medical communication center(s)”, as this provides clarity and precision regarding the primary function and purpose of the center.